Anemia In Adolescents Based on BMI (Body Mass Index) and Menstrual Cycle - Sari, Dwi Siska Mayang; Azizah, Nurul; Purwanti, Yanik; Rinata, Evi (Universitas Islam Lamongan, 2024)
Anemia is one of the global health issues. There was an increase in the prevalence of anemia in the 15 24 age group from 2014 to 2018, rising from 18.4% to 32%. Anemia in adolescents impacts concentration ability, immunity, cognitive function, and poses risks such as giving birth to low birth weight (LBW) babies and stunting. This study aims to determine the relationship between Body Mass Index (BMI) and Menstrual Cycle with the incidence of anemia in adolescents. The research employed a quantitative approach with a cross-sectional design. The population consisted of 60 individuals, with sample collection conducted using the total sampling technique. Data analysis was carried out using the chi-square statistical test. The study showed that almost all adolescent girls with anemia had abnormal BMI (96.4%) and abnormal menstrual cycles (75.9%). Statistical tests revealed a significant relationship between anemia and BMI (P-value=0.001) and menstrual cycle (P-value=0.001) among adolescent girls. There is a significant relationship between BMI and menstrual cycle with the incidence of anemia in adolescent girls. BMI and menstrual cycle are factors contributing to anemia, thus requiring interventions targeting nutritional status and menstrual health among adolescent girls by raising awareness and promoting the habit of consuming healthy and balanced nutritious food.